Social interaction reward in rats has anti‐stress effects. (26th January 2020) - Lemos, Cristina; Salti, Ahmad; Amaral, Inês M.; Fontebasso, Veronica; Singewald, Nicolas; Dechant, Georg; Hofer, Alex; El Rawas, Rana
Abstract: Social interaction in an alternative context can be beneficial against drugs of abuse. Stress is known to be a risk factor that can exacerbate the effects of addictive drugs. In this study, we investigated whether the positive effects of social interaction are mediated through a decrease in stress levels. For that purpose, rats were trained to express cocaine or social interaction conditioned place preference (CPP). Behavioural, hormonal, and molecular stress markers were evaluated. We found that social CPP decreased the percentage of incorrect transitions of grooming and corticosterone to the level of naïve untreated rats. In addition, corticotropin‐releasing factor (CRF) was increased in the bed nucleus of stria terminalis after cocaine CPP. In order to study the modulation of social CPP by the CRF system, rats received intracerebroventricular CRF or alpha‐helical CRF, a nonselective antagonist of CRF receptors. The subsequent effects on CPP to cocaine or social interaction were observed. CRF injections increased cocaine CPP, whereas alpha‐helical CRF injections decreased cocaine CPP. However, alpha‐helical CRF injections potentiated social CPP. When social interaction was made available in an alternative context, CRF‐induced increase of cocaine preference was reversed completely to the level of rats receiving cocaine paired with alpha‐helical CRF. This reversal of cocaine preference was also paralleled by a reversal in CRF‐induced increase of p38 MAPK expression in the nucleus accumbens shell. These findings suggest that social interaction could contribute as a valuable component in treatment of substance use disorders by reducing stress levels. Abstract : SI has anti‐stress effects? Rats that express SI CPP, show decreased markers of stress to the level of naive untreated rats. SI preference is potentiated by alpha‐helical CRF (a non‐selective CRF receptor antagonist) but is not affected by CRF icv injections. Cocaine preference is potentiated by icv CRF injections. However, alpha‐helical CRF icv injections or the availability of positive social interaction as an alternative to cocaine, abolish cocaine preference and decrease markers of stress. Thus, SI reward in an alternative context in rats is beneficial against cocaine by reducing stress levels. SI = social interaction; CPP = conditioned place preference; icv = intracerebroventricular; CRF = corticotropin‐releasing factor.